Richard Stoddert Ewell papers - Ewell, Richard Stoddert, 1817-1872.
Chiefly letters from Ewell to his family and others concerning army life, the Mexican War, the Civil War, and his imprisonment at Fort Warren, Mass. Includes accounts of the Gettysburg and Peninsular campaigns and the use of blacks as soldiers by the Confederacy. Correspondents include Jefferson Davis, Jubal Anderson Early, Henry Jackson Hunt, Joseph E. Johnston, Robert E. Lee, Charles Marshall, Dabney Herndon Maury, Lafayette McLaws, and William T. Sherman.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
In part, photocopies.
U.S. and Confederate Army officer.
Collection material in English.
Keywords: Davis, Jefferson, -- 1808-1889 -- Correspondence; Early, Jubal Anderson, -- 1816-1894 -- Correspondence; Hunt, Henry Jackson, -- 1819-1889 -- Correspondence; Johnston, Joseph E. -- 1807-1891 -- Correspondence; Lee, Robert E. -- 1807-1870 -- Correspondence; Marshall, Charles, -- 1830-1902 -- Correspondence; Maury, Dabney Herndon, -- 1822-1900 -- Correspondence; McLaws, Lafayette, -- 1821-1897 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Confederate States of America. -- Army -- African American troops; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Mexican War, 1846-1848.; Peninsular Campaign, 1862.; Prisoners -- Massachusetts; Fort Warren (Mass.); Massachusetts -- History -- Civil War, 1861-1865.; Pennsylvania -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Participation, African American; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Virginia -- History -- Civil War, 1861-1865.; Army officers, Confederate